Hepatoprotective Potential of Propolis toward Hepar Injury Rats (Rattus norvegicus) Induced by Carbon Tetrachloride - Diah Krisnansari; Hidayat Sulistyo; Wahyu Dwi Kusdaryantoi (Universitas Airlangga, 2014)
Introduction: The prevalence of chronic liver disease continues to increase. One potentially hepatotoxic substances that cause chronic liver disease is carbon tetrachloride. The process of liver damage can be prevented by the antioxidant role of propolis. The aims of this research was to study the hepatoprotective potential of propolis toward hepar injury rats induced by carbon tetrachlorida.Method: This was an experimental study with pre-post test. Twenty five male Wistar rats aged 12–16 week old, weighing 125–200 gr were allocated into 5 groups. Group I: standard meal + aquadest-gavage; group II: standard meal + CCl4 1% 1 mL + aquadest-gavage, group III: standard meal + CCl4 1% 1 mL + 0,054 gr propolis-gavage, group IV: standard meal + CCl4 1% 1 mL + 0,108 gr propolis-gavage and group V: standard meal + CCl4 1% 1 mL + sylimarin 50 mg/kg-gavage. IL-6, SOD, NAS score+fibrotic were measured after treatment. Analysed of IL-6 and NAS score+fibrotic with Kruskal Wallis to Mann Whitney and analysed of SOD with One-Way ANOVA to LSD.Results: The study showed that there were significant differences in IL-6, SOD and NAS score + fibrotic between groups.Discussion: Provision of 0,054 gr and 0,108 gr have hepatoprotective potential toward hepar injury rats induced by carbon tetrachlorida. Further research need to identify antioxidants and hepatoprotective potential of propolis on human with liver disease.